Repeatability of metabolic tumor burden and lesion glycolysis between clinical readers - Choi, Jung W.; Dean, Erin A.; Lu, Hong; Thompson, Zachary; Qi, Jin; Krivenko, Gabe; Jain, Michael D.; Locke, Frederick L.; Balagurunathan, Yoganand (Frontiers in Immunology, 2023)
It has been shown that Metabolic Tumor Volume (MTV) and Tumor Lesion Glycolysis (TLG) are prognostic biomarkers for clinical outcome in diffuse large B-cell lymphoma (DLBCL). They provide a gross measure of the disease burden that is considered prognostic to treatment response. The definition of these measurements has not been rigorously standardized, leading to sources of variation upon further quantitative evaluation. In this study these parameters were semi-automated on clinical PET/CT images. Parameters for all lesions were derived from standard uptake values (SUVs) over a 41% threshold. We systematically contrasted MTV computation differences between expert readers using two different processes. One reader manually corrected regional boundaries after automated detection performed across the lesions in a body scan (Reader M using a manual process, or manual). The other reader used a semi-automated method of lesion identification, where after detection they had the option to delete tumor lesion, without any boundary modification, based on their judgment (Reader A using a semi- automated process, or auto). We find that MTVs computed for Readers M and A ) were both concordant (concordant correlation coefficient of 0.96) and prognostic with a P-value of 0.0001 and 0.0002 respectively for overall survival after treatment. Additionally, we find Tumor Glycolytic Volume for these reader approaches showed concordance (CCC of 0.96) and was prognostic for over -all survival (p-value of 0.0001 for both). In conclusion, the semi-automated expert reader assisted approach provides acceptable quantification of tumor burden by MTV or TLG on PET/CT scans.